A targeted ferritin-microplasmin based thrombolytic nanocage selectively dissolves blood clots - Seo, Junyoung; Al-Hilal, Taslim A.; Jee, Jun-Goo; Kim, Yong-Lim; Kim, Ha-Jeong; Lee, Byung-Heon; Kim, Soyoun; Kim, In-San (ELSEVIER, 2018)
The use of thrombolytic therapies is limited by an increased risk of systemic hemorrhage due to lysis of hemostatic clots. We sought to develop a plasmin-based thrombolytic nanocage that efficiently dissolves the clot without causing systemic fibrinolysis or disrupting hemostatic clots. Here, we generated a double chambered short-length ferritin (sFt) construct that has an N-terminal region fused to multivalent clot targeting peptides (CLT: CNAGESSKNC) and a C-terminal end fused to a microplasmin (mu Pn); CLT recognizes fibrin-fibronectin complexes in clots, mu Pn efficiently dissolves clots, and the assembly of double chambered sFt (CLT-sFt-mu Pn) into nanocage structure protects the activated-mu Pn from its circulating inhibitors. Importantly, activated CLT-sFt-mu Pn thrombolytic nanocage showed a prolonged circulatory life over activated-mu Pn and efficiently lysed the preexisting clots in both arterial and venous thromboses models. Thus, CLT-sFt-mu Pn thrombolytic nanocage platform represents the prototype of a targeted clot-busting agent with high efficacy and safety over existing thrombolytic therapies. (c) 2018 Elsevier Inc. All rights reserved.
Keywords: TISSUE-PLASMINOGEN ACTIVATOR; ACUTE ISCHEMIC-STROKE; PLATFORM; NANOPARTICLES; MECHANISMS; THROMBOSIS; PEPTIDES; DELIVERY; HEPARIN; ACID